Investigation of Some Performance Characteristics and Handball Talent Levels of Male and Female Students - İdris Kayantaş; Harun Genç; Gökmen Kılnçarslan; Akan Bayraktar (Selcuk University, 2018)
In this study, it was aimed to determine the performance characteristics and skill levels specific to the sport branch and to determine the talent and to direct the correct branch while the children with very high potential in our country are directed to the spore. The sample group of this study consisted of 124 volunteer middle school students, 62 girls 11,13 years and 62 boys 11,06 years, aged, who had never been trained in any sport branch in Ankara. The performance features include a vertical jump test, a long jump test, a 20 m speed run test, a health ball throw test, and a hand throw test for handball talent detection, triple jump shooting, throwing ball, throwing ball to the target on the wall, test was applied. Statistical analyzes of the measurements were made in the SPSS 22 program. When the total scores of the male and female students who applied the handball ability test battery were examined, it is determined that there are 17 female and 22 male students with good and very good level. As a result; It is thought that 15 male and 11 female learners may be more successful in the handball field than other students and therefore it is appropriate to direct these students to the handball branch.